IMPLEMENTASI MODEL PEMBELAJARAN KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN AKTIVITAS BELAJAR DAN HASIL BELAJAR PESERTA DIDIK SUB POKOK BAHASAN MENGELOLA KARTU PERSEDIAAN PADA PESERTA DIDIK KELAS XI.111.2 SMK PGRI 2 NGANJUK TAHUN AJARAN 2019/2020 - Aini, Siti Nurul (CV Sintesia, 2025)
In learning activities, the learning model applied by the teacher in the classroom greatly affects the achievement or learning outcomes of students, so it requires the mental involvement and work of the students themselves in order to produce meaningful learning outcomes. Only active learning activities can produce meaningful and unforgettable learning outcomes. In a study entitled Implementation of the Jigsaw Type Cooperative Learning Model to Improve Learning Activities and Learning Outcomes of Students, the Sub-topic of Managing Inventory Cards for Class XI.111.2 Students SMK PGRI 2 Nganjuk School year 2019/2020. learning activities have not achieved optimal results. This happens because during learning activities the learning activities of students are still lacking, so the impact on the learning outcomes achieved is also less than optimal. This research was carried out in 1 cycle, in which cycle 1 consisted of 2 (two) face-to-face meetings. The results of this study are, that there is an increase in student learning activities for each indicator. This increase in learning activities occurs because the jigsaw type cooperative learning model involves more students in learning activities. The reciprocal relationship between students and teachers and with other students is more balanced, thus creating a more active and enjoyable learning atmosphere. It can be proven that before the application of the jigsaw type cooperative learning model the average student learning activity was 55.07%. After the application of the jigsaw type cooperative learning model, the average student learning activity increased to 75.00%. With the increase in student learning activities, in the end it is also able to improve the learning outcomes achieved by students. It can be seen that before the application of the jigsaw type cooperative learning model the average scores of students was 69.90. From the number of students as many as 31 people, who finished studying (scores above KKM 65) were 20 people (64.52%), while the number of students who had not completed (scores below KKM 65) were 11 people (35.48%). However, after the application of the jigsaw type cooperative learning model in learning activities, student learning outcomes have increased. From the number of students as many as 31 people, who finished studying (scores above KKM 65) were 25 people (80.65%), while the number of students who had not completed (scores below KKM 65) decreased by 6 people (19, 35%). For the average scores of the class also increased to 73.16.